2024
DOI: 10.1038/s42005-024-01570-4
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Josephson vortex-based memory cell with microwave energy-efficient readout

Dmitrii S. Kalashnikov,
Vsevolod I. Ruzhitskiy,
Andrey G. Shishkin
et al.

Abstract: The ongoing progress of superconducting logic systems with Josephson junctions as base elements requires the development of compatible cryogenic memory. Long enough junctions subject to magnetic field host quantum phase 2π-singularities—Josephson vortices. Here, we report the realization of the superconducting memory cell whose state is encoded by the number of present Josephson vortices. By integrating the junction into a coplanar resonator and by applying a microwave excitation well below the critical curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The developed equation in methodology section EQUATION ( 14) and EQUATION ( 9) and to study the nature of developed equation was computed using MATLAB and for this data form [26][27][28] and study the nature of JPD with temperature and with fermi velocity as shown in FIGURE 1 and 2 respectively. The nature of Josephson penetration Depth (JPD) to electronphonon and transition temperature in FIGURE 1 shoes that JPD decrease with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed equation in methodology section EQUATION ( 14) and EQUATION ( 9) and to study the nature of developed equation was computed using MATLAB and for this data form [26][27][28] and study the nature of JPD with temperature and with fermi velocity as shown in FIGURE 1 and 2 respectively. The nature of Josephson penetration Depth (JPD) to electronphonon and transition temperature in FIGURE 1 shoes that JPD decrease with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Integration into coplanar resonators enables scalability and compatibility with superconducting microwave technologies. Additionally, NbN/Au nanogaps bridged with Al superconductor exhibit high critical current density and Josephson coupling, highlighting the importance of superconducting barriers for achieving high Josephson current in nanodevices, crucial for superconducting circuits with high integration density [27][28].…”
Section: Perturbed Sine-gordon Equationmentioning
confidence: 99%